2017
DOI: 10.3389/fmicb.2017.01767
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Potential of Acyclic Amines and Diamines against Multi-Drug Resistant Staphylococcus aureus

Abstract: Multi-drug resistant Staphylococcus aureus (MDRSA) remains a great challenge despite a decade of research on antimicrobial compounds against their infections. In the present study, various acyclic amines and diamines were chemically synthesized and tested for their antimicrobial as well as antibiofilm activity against MDRSA. Among all the synthesized compounds, an acyclic diamine, (2,2′-((butane-1,4-diylbis(azanediyl)bis(methylene))diphenol) designated as ADM 3, showed better antimicrobial activity (minimum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…MBC was determined by performing viable count (CFU/mL) following 24 h of incubation at 37°C and was defined as the lowest medicament concentration that reduced the viable cells by more than 3 log10 steps (>99.9%) compared to the untreated control cultures. Independent assays were performed in triplicates ( Gahlaut and Chhillar, 2013 ; Clinical and Laboratory Standards Institute [CLSI], 2016 ; Kaur et al, 2017 ). The antimicrobial synergy effect of different medicaments combinations was also evaluated in vitro using Checkerboard method as previously described by Tin et al (2009) .…”
Section: Methodsmentioning
confidence: 99%
“…MBC was determined by performing viable count (CFU/mL) following 24 h of incubation at 37°C and was defined as the lowest medicament concentration that reduced the viable cells by more than 3 log10 steps (>99.9%) compared to the untreated control cultures. Independent assays were performed in triplicates ( Gahlaut and Chhillar, 2013 ; Clinical and Laboratory Standards Institute [CLSI], 2016 ; Kaur et al, 2017 ). The antimicrobial synergy effect of different medicaments combinations was also evaluated in vitro using Checkerboard method as previously described by Tin et al (2009) .…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotics resistant state of the biofilm cells lead to a treatment complications in the series of human infections which include biofilm formation on various biological implants such as, heart catheters, urinary catheters, joint implants and replacement of heart valves [120]. Biofilms pose a threat to the human race because of their persistent nature and plays a major role in certain pathogenic infections [40, 58, 104, 120]. Studies suggested that role of EPS have been conferring tolerance to aminoglycosides [41, 61].…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated furanone isolated from Delisea pulchra (marine algae) interrupt the bacterial QS signalling [74]. Recently, Kaur et al [58] reported an acyclic diamine (ADM 3), showed better antimicrobial activity and antibiofilm activity [58]. Attenuation of bacterial QS signalling by ginseng extract, garlic extract, usnic acid and azithromycin possesses inhibitory activity against bacterial and fungal biofilms [18, 51, 122].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DMTU blocks the expression of virulence factors controlled by the QS system, such as the biofilm formation [2]. Besides, according to in vitro assays, DMTU down-regulates some genes involved in the expression of various virulence factors regulated through QS in S. mutans [7].…”
Section: Introductionmentioning
confidence: 99%